Film and manufacturing method thereof
Patent Information
- Application Number
- JP2022205378
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-12-22
AI Technical Summary
【0013】 本発明により、耐擦過性及びフィルムが貼り付けられたペン入力デバイスに対してペン型ポインティングデバイスにより情報入力する際の書き味に優れ、且つ取り扱いやすさ(屈曲性)にも優れるフィルム、及びフィルムの製造方法を提供することができる。
Smart Images

Figure 0007644081000001 
Figure 0007644081000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a film and a method for producing the same. [Background technology]
[0002] In recent years, it has become common to input information into information devices such as smartphones, notebook computers, tablets, etc., via information input panels such as touch panels. In particular, in pen input devices that allow information input using a pen-type pointing device such as a stylus pen, such as pen tablets, liquid crystal tablets, tablet-type personal computers, and electronic paper, the pen-type pointing device is used for purposes such as writing characters and drawing pictures.
[0003] As pen input devices have come to be used for various purposes, various advanced functions have been required for input methods using pen-type pointing devices. For example, when a pen-type pointing device is directly used as a pen input device, the tip of the pen slips and the writing feel is poor, so a function that provides an appropriate writing resistance and adds a writing feel similar to that of writing with a pencil on paper is required.
[0004] In order to provide the above-mentioned writing feel, various films for pen input devices have been proposed.
[0005] For example, Patent Document 1 discloses a laminated film for touch panels in which silica fine particles are contained in a hard coat layer and which has a convex shape on the surface.
[0006] Furthermore, Patent Document 2 discloses a film for improving the feel of a material, the surface of which is given a convex shape by the shape of the resin. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent Publication No. 2010-153298
Patent Document 2
Summary of the Invention
Problems to be Solved by the Invention
[0008] However, the laminated film for a touch panel described in Patent Document 1 has a problem that when information is input by a pen-type pointing device, the silica fine particles on the hard coat layer are likely to drop out, and the surface of the film is likely to be scratched.
[0009] Further, the tactile improvement film described in Patent Document 2 has a problem that when information is input by a pen-type pointing device, the convex portions of the resin are likely to drop out, and the surface of the film is likely to be scratched (i.e., poor scratch resistance).
[0010] The present invention has been made in view of such circumstances, and an object of the present invention is to provide a film that is excellent in scratch resistance, writing feel when information is input by a pen-type pointing device with respect to a pen input device to which the film is attached, and handling ease (flexibility), and a method for manufacturing the film.
Means for Solving the Problems
[0011] As a result of intensive studies to solve the above problems, the present inventors have found that a film having valleys and mountains conforming to JIS B0601:2001 on the surface, wherein the maximum valley depth (Rv) of the valleys conforming to JIS B0601:2001, the maximum peak height (Rp) of the mountains, and the average length of the elements (RSm) satisfy 1.50 μm < Rv < 8.00 μm, 0.80 < Rv / (Rv + Rp) < 0.90, and 30 μm < RSm < 300 μm, the storage elastic modulus of the film is 0.052 to 1.500 GPa, and the film contains a UV curable resin. By using the film, the above problems can be solved, and the present invention has been completed.
[0012] That is, the present invention is as follows. (1) A film having a surface with valleys and peaks conforming to JIS B0601:2001, The maximum valley depth (Rv) of the valley, the maximum peak height (Rp) of the peak, and the average length (RSm) of the element in accordance with JIS B0601:2001, 1.50μm <Rv<8.00μm 0.80 <Rv / (Rv+Rp)<0.90 30μm <RSm<300μm Fulfilling The storage modulus of the film is 0.052 GPa to 1.500 GPa, The film includes a UV-curable resin. film. (2) does not contain particulates to form said valleys and / or peaks on said surface; The film described in (1). (3) The storage modulus of the film is 0.150 GPa to 1.000 GPa. A film according to (1) or (2). (4) The UV curable resin includes at least one selected from the group consisting of (meth)acrylate oligomers and (meth)acrylate monomers. A film according to (1) or (2). (5) The (meth)acrylate oligomer includes at least one selected from the group consisting of a urethane (meth)acrylate oligomer, an acrylic resin (meth)acrylate oligomer, an epoxy (meth)acrylate oligomer, and a polyester (meth)acrylate oligomer; The (meth)acrylate monomer includes at least one selected from the group consisting of isobornyl (meth)acrylate monomer, tripropylene glycol di(meth)acrylate monomer, tetrahydrofurfuryl (meth)acrylate monomer, phenoxyethyl (meth)acrylate monomer, dipentaerythritol hexa(meth)acrylate monomer, tricyclodecane dimethanol di(meth)acrylate monomer, benzyl (meth)acrylate monomer, stearyl (meth)acrylate monomer, isodecyl (meth)acrylate monomer, isoctyl (meth)acrylate monomer, 1,6-hexanediol di(meth)acrylate monomer, lauryl (meth)acrylate monomer, m-phenoxybenzyl (meth)acrylate monomer, isoamyl (meth)acrylate monomer, phenoxydiethylene glycol (meth)acrylate monomer, and 1,4-butanediol di(meth)acrylate monomer; The film described in (4). (6) The film further comprises a photoinitiator. A film according to (1) or (2). (7) A film for a pen input device. A film according to (1) or (2). (8) A method for producing a film, comprising: a coating step of coating a UV-curable resin composition; and a step of forming valleys and peaks in accordance with JIS B0601:2001 on a surface of the film by transfer using a positive mold, The film has a maximum valley depth (Rv) of the valley, a maximum peak height (Rp) of the peak, and an average element length (RSm) in accordance with JIS B0601:2001. 1.50μm <Rv<8.00μm 0.80 <Rv / (Rv+Rp)<0.90 30μm <RSm<300μm Fulfilling The storage modulus of the film is 0.052 GPa to 1.500 GPa, The film includes a UV-curable resin. Method for manufacturing a film
Effect of the Invention
[0013] According to the present invention, it is possible to provide a film that is excellent in abrasion resistance, writing feel when inputting information with a pen-type pointing device to a pen input device to which the film is attached, and also excellent in handleability (flexibility), and a method for manufacturing the film.
Embodiment for Carrying Out the Invention
[0014] Hereinafter, embodiments for carrying out the present invention (hereinafter referred to as "the present embodiment") will be described in detail. Note that the present invention is not limited to the following embodiments, and various modifications can be made and implemented within the scope of the gist thereof. The "~" of the numerical range means a range including the numerical values before and after it. For example, "0 mass% to 100 mass%" means a range that is 0 mass% or more and 100 mass% or less.
[0015] 1. Film The film according to the present embodiment is a film having valleys and mountains conforming to JIS B0601:2001 on the surface, and the maximum valley depth (Rv) of the valleys conforming to JIS B0601:2001, the maximum peak height (Rp) of the mountains, and the average length (RSm) of the elements satisfy 1.50 μm < Rv < 8.00 μm, 0.80 < Rv / (Rv + Rp) < 0.90, and 30 μm < RSm < 300 μm. The storage elastic modulus of the film is 0.052 to 1.500 GPa, and the film contains a UV curable resin.
[0016] The film according to the present embodiment is not particularly limited. For example, it is used by being attached to substrates of various shapes (curved surfaces, flat surfaces, etc.) and various materials (glass, acrylic resin, polyacetal resin, etc.).
[0017] When the film satisfies the relationships of 1.50 μm < Rv < 8.00 μm, 0.80 < Rv / (Rv + Rp) < 0.90, and 30 μm < RSm < 300 μm, it tends to have excellent abrasion resistance and excellent writing feel when inputting information with a pen-type pointing device to a pen input device to which the film is attached. Also, when the storage elastic modulus of the film is 0.052 to 1.500 GPa, it tends to have excellent abrasion resistance and flexibility. Further, by including a UV curable resin, it tends to have excellent abrasion resistance and excellent moldability.
[0018] The reason why the film tends to have excellent abrasion resistance when it satisfies the relationships of 1.50 μm < Rv < 8.00 μm, 0.80 < Rv / (Rv + Rp) < 0.90, and 30 μm < RSm < 300 μm is considered to be to suppress the formation of large mountains which are mountains conforming to JIS B0601:2001 on the surface of the film, so that a part or all of the surface of the film does not fall off due to friction and the surface of the film is not damaged. Also, the reason why it tends to have excellent writing feel when inputting information with a pen-type pointing device to a pen input device to which the film is attached when it satisfies the above-mentioned relationships is considered to be to provide an appropriate resistance when inputting information with a pen-type pointing device through the pen input device to which the film is attached by promoting the formation of valleys of an appropriate size which are valleys conforming to JIS B0601:2001. However, the reasons for the tendency to have excellent abrasion resistance and excellent writing feel when inputting information with a pen-type pointing device to a pen input device to which the film is attached are not limited to this.
[0019] When the storage modulus of the film is 0.052 to 1.500 GPa, the film tends to have excellent abrasion resistance and bending properties. When the storage modulus of the film is 0.052 GPa or more, the film exhibits appropriate hardness. This makes it possible to prevent the film from being partially or completely chipped off due to friction and the film surface from being scratched (i.e., excellent abrasion resistance). When the storage modulus of the film is 1.500 GPa or less, the film exhibits appropriate flexibility. This makes it possible to bond the film to substrates of various shapes (curved surface, flat surface, etc.) and various materials (glass, acrylic resin, polyacetal resin, etc.) without causing cracks on the surface (i.e., excellent bending resistance). However, the factors that tend to have excellent abrasion resistance and bending properties are not limited to the above.
[0020] The film of the present embodiment tends to have excellent abrasion resistance, writing feel when inputting information with a pen-type pointing device through a pen input device to which the film is attached, and flexibility, and is therefore suitable for use as a film for a pen input device. The pen input device is not particularly limited as long as it is a display device that allows information to be input with a pen-type pointing device such as a stylus pen, and examples thereof include a pen tablet, a liquid crystal tablet, a tablet-type personal computer, and electronic paper.
[0021] Each component of the film of this embodiment (hereinafter also simply referred to as "film") will be described in detail below, but the present invention is not limited thereto, and various modifications are possible without departing from the gist of the present invention.
[0022] The film is produced by the method described below using a UV-curable resin composition as a raw material. The UV-curable resin composition contains a UV-curable resin described in detail below, and may contain a photopolymerization initiator and other additives.
[0023] 1.1.UV curable resin The UV-curable resin in this embodiment means a resin that is cured by UV irradiation. The UV-curable resin is not particularly limited, but may be, for example, a (meth)acrylate oligomer or a (meth)acrylate monomer, and each of these may be used alone or in combination of two or more.
[0024] The specific structure of the (meth)acrylate oligomer is not particularly limited, and examples thereof include urethane (meth)acrylate oligomer, acrylic resin (meth)acrylate oligomer, epoxy (meth)acrylate oligomer, polyester (meth)acrylate oligomer, alkane (meth)acrylate oligomer, and alkylene glycol (meth)acrylate oligomer. Among these, it is preferable to include one or more selected from the group consisting of urethane (meth)acrylate oligomer, acrylic resin (meth)acrylate oligomer, epoxy (meth)acrylate oligomer, and polyester (meth)acrylate oligomer, and it is more preferable to include urethane (meth)acrylate oligomer. By using the (meth)acrylate oligomer, the flexibility tends to be improved.
[0025] The (meth)acrylate monomer is preferably compatible with the (meth)acrylate oligomer. The specific structure of the (meth)acrylate monomer is not particularly limited, but may be, for example, methyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, propyl (meth)acrylate monomer, isopropyl (meth)acrylate monomer, butyl (meth)acrylate monomer, isoamyl (meth)acrylate monomer, hexyl (meth)acrylate monomer, 2-ethyl (meth)acrylate monomer, isoctyl (meth)acrylate monomer, isodecyl (meth)acrylate monomer, lauryl (meth)acrylate monomer, stearyl (meth)acrylate monomer, isobornyl (meth)acrylate monomer, cyclohexyl (meth)acrylate monomer ...ethyl (meth)acrylate monomer, isoctyl (meth)acrylate monomer, isodecyl (meth)acrylate monomer, lauryl (meth)acrylate monomer, stearyl (meth)acrylate monomer, isobornyl (meth)acrylate monomer, cyclohexyl (meth)acrylate monomer, methyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, ethyl (meth)acrylate monomer, ethyl (meth) Examples of the ether group-containing acrylate monomer include ether group-containing acrylate monomers such as acrylate monomers, alkyl (meth)acrylate monomers such as benzyl acrylate, tripropylene glycol di(meth)acrylate monomer, tetrahydrofurfuryl (meth)acrylate monomer, phenoxyethyl (meth)acrylate monomer, dipentaerythritol hexa(meth)acrylate monomer, tricyclodecane dimethanol di(meth)acrylate monomer, 1,6-hexanediol di(meth)acrylate monomer, phenoxydiethylene glycol (meth)acrylate monomer, 1,4-butanediol di(meth)acrylate monomer, and m-phenoxybenzyl (meth)acrylate monomer.Among these, isobornyl (meth)acrylate monomer, tripropylene glycol di(meth)acrylate monomer, tetrahydrofurfuryl (meth)acrylate monomer, phenoxyethyl (meth)acrylate monomer, dipentaerythritol hexa(meth)acrylate monomer, tricyclodecane dimethanol di(meth)acrylate monomer, benzyl (meth)acrylate monomer, stearyl (meth)acrylate monomer, isodecyl (meth)acrylate monomer, isoctyl (meth)acrylate monomer, 1,6-hexanediol di(meth)acrylate monomer, lauryl (meth)acrylate monomer It is preferable that the monomer contains at least one selected from the group consisting of m-phenoxybenzyl (meth)acrylate monomer, isoamyl (meth)acrylate monomer, phenoxydiethylene glycol (meth)acrylate monomer, and 1,4-butanediol di(meth)acrylate monomer, and it is more preferable that the monomer contains at least one selected from the group consisting of isobornyl (meth)acrylate monomer, tripropylene glycol di(meth)acrylate monomer, tetrahydrofurfuryl (meth)acrylate monomer, phenoxyethyl (meth)acrylate monomer, and dipentaerythritol hexa(meth)acrylate monomer. By using a (meth)acrylate monomer, the physical properties such as the storage modulus, refractive index, durability, and viscosity of the film can be set within a suitable range.
[0026] Low-viscosity (meth)acrylate monomers are suitable for diluting UV-curable resin compositions. Examples of low-viscosity (meth)acrylate monomers include, but are not limited to, isobornyl (meth)acrylate monomer, tripropylene glycol di(meth)acrylate monomer, tetrahydrofurfuryl (meth)acrylate monomer, and phenoxyethyl (meth)acrylate monomer. In this specification, low-viscosity (meth)acrylate monomer refers to a (meth)acrylate monomer having a viscosity of 2 Pa·s or less at 25°C.
[0027] A (meth)acrylate monomer having a glass transition temperature of 80° C. or higher is preferably used to increase the storage modulus of the UV-curable resin composition. The (meth)acrylate monomer having a glass transition temperature of 80° C. or higher is not particularly limited, but examples thereof include dipentaerythritol hexa(meth)acrylate monomer and isobornyl(meth)acrylate monomer.
[0028] The (meth)acrylate monomer having a glass transition temperature of 5° C. or less is preferably used to reduce the storage modulus of the UV-curable resin composition. The (meth)acrylate monomer having a glass transition temperature of 5° C. or less is not particularly limited, but may be, for example, a phenoxyethyl (meth)acrylate monomer.
[0029] The polyfunctional (meth)acrylate monomer is preferably used to adjust the crosslink density of the UV-curable resin composition and increase the storage modulus. In this specification, the polyfunctional (meth)acrylate monomer refers to a (meth)acrylate monomer having two or more functional groups of the same or different structures in one molecule. The functional group is not particularly limited, but examples thereof include an acryloyl group, an epoxy group, and a carboxy group.
[0030] The polyfunctional (meth)acrylate monomer is not particularly limited, but examples thereof include a difunctional tripropylene glycol di(meth)acrylate monomer and a hexafunctional dipentaerythritol hexaacrylate monomer.
[0031] The (meth)acrylate monomer having solubility in plastics is preferably used because of its excellent adhesiveness to the substrate film described below. The (meth)acrylate monomer having solubility in plastics is not particularly limited, but may be, for example, tetrahydrofurfuryl (meth)acrylate monomer.
[0032] The content of the UV curable resin is preferably 45 to 99 mass%, 50 to 99 mass%, 60 to 99 mass%, 70 to 99 mass%, or 80 to 99 mass% based on the total solid content of the UV curable resin composition. When the content of the UV curable resin is within the above range, the abrasion resistance and bending property tend to be excellent.
[0033] The content of the (meth)acrylate oligomer is preferably 15.0 to 70.0 mass%, 20.0 to 65.0 mass%, 30.0 to 60.0 mass%, 33.0 to 55.0 mass%, or 35.0 to 50.0 mass% relative to the total solid content of the UV-curable resin composition. When the content of the (meth)acrylate oligomer is within the above range, the abrasion resistance and flexibility tend to be excellent.
[0034] The content of the (meth)acrylate oligomer is preferably 20.0 to 80.0 mass%, 25.0 to 70.0 mass%, 30.0 to 60.0 mass%, 33.0 to 50.0 mass%, or 35.0 to 50.0 mass% relative to the total solid content of the UV-curable resin. When the content of the (meth)acrylate oligomer is within the above range, the abrasion resistance and flexibility tend to be excellent.
[0035] The content of the (meth)acrylate monomer is preferably 30.0 to 80.0 mass%, 40.0 to 70.0 mass%, 50.0 to 65.0 mass%, or 50.0 to 60.0 mass% based on the total solid content of the UV-curable resin composition. When the content of the (meth)acrylate monomer is within the above range, the abrasion resistance and flexibility tend to be excellent.
[0036] The content of the (meth)acrylate monomer is preferably 35.0 to 85.0 mass%, 40.0 to 70.0 mass%, 50.0 to 67.0 mass%, or 50.0 to 65.0 mass% relative to the total solid content of the UV-curable resin. When the content of the (meth)acrylate monomer is within the above range, the abrasion resistance and flexibility tend to be excellent.
[0037] 1.2. Photopolymerization initiator The film of the present embodiment preferably contains a photopolymerization initiator. The photopolymerization initiator of the present embodiment is not particularly limited, but examples thereof include carbonyl compounds such as acetophenone, benzophenone, benzyl, benzoin, acylphosphine oxide, benzoin benzoate, and α-acyloxime ester, sulfur compounds such as tetramethylthiuram monosulfide and thioxanthones, and phosphorus compounds such as diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, and the like. Each of these may be used alone or in combination of two or more.
[0038] The specific structure of the photopolymerization initiator is not particularly limited, but examples thereof include 1-hydroxycyclohexyl phenyl ketone and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide.
[0039] The content of the photopolymerization initiator is preferably 0.1 to 10 mass%, 0.5 to 8 mass%, or 1 to 5 mass%, based on the total solid content of the UV-curable resin composition. When the content of the photopolymerization initiator is within the above range, the curing speed, flexibility, and abrasion resistance tend to be excellent.
[0040] 1.3.Other Additives In addition to the above-mentioned components, the film of the present embodiment may contain other known components that can be used in conventional films. The other components are not particularly limited, but may include colorants, antioxidants, photopolymerization accelerators, ultraviolet absorbers, light stabilizers, flame retardants, fillers, adhesives, and other additives. The other components may be used alone or in combination of two or more.
[0041] 1.4.Other The film of this embodiment may be a single layer film made of a UV-curable resin composition, or may be a laminated film made of a surface layer film made of a UV-curable resin composition and a substrate film supporting the surface layer film. The method of attaching the film of this embodiment to the substrate is not particularly limited, and examples thereof include a method of directly attaching a single layer film to a substrate, and a method of attaching a substrate film of a laminated film and a substrate via an adhesive. In the case of a laminated film, each of the above-mentioned components is each of the components of the surface layer film. Here, the substrate is not particularly limited, and is, for example, a member of the surface of a pen input device, specifically, glass, acrylic resin, polyacetal resin, etc. The components of the substrate film are not particularly limited, and examples thereof include the above-mentioned UV-curable resin, thermosetting resin, and thermoplastic resin.
[0042] Examples of the thermosetting resin include phenol resin, epoxy resin, melamine resin, urea resin, polyurethane, and thermosetting polyimide.
[0043] Examples of the thermoplastic resin include polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyamide, polyethylene terephthalate, thermoplastic polyimide, cellulose acetate, and polyethylene naphthalate.
[0044] In addition to the above components, the base film may contain other known components that can be used in conventional films. The other components are not particularly limited, but may include colorants, stabilizers, flame retardants, fillers, adhesives, and other additives. The other components may be used alone or in combination of two or more.
[0045] 2. Film characteristics Each characteristic of the film of this embodiment (hereinafter also simply referred to as "film") will be described in detail below, but the present invention is not limited thereto, and various modifications are possible without departing from the gist of the present invention.
[0046] 2.1.Surface structure The surface of the film has an uneven shape, where the concave shape is a valley conforming to JIS B0601:2001, and the convex shape is a peak conforming to JIS B0601:2001. Also, the average length (RSm) of the elements conforming to JIS B0601:2001 is the average length between valleys.
[0047] The maximum valley depth (Rv) conforming to JIS B0601:2001 is 1.50 μm < Rv < 8.00 μm, preferably 2.00 μm < Rv < 7.50 μm, and 2.50 μm < Rv < 7.00 μm. When Rv is within the above range, the film has excellent abrasion resistance and writing feel when information is input by a pen-type pointing device to a pen input device to which the film is attached. The maximum valley depth (Rv) conforming to JIS B0601:2001 can be measured in accordance with JIS B0601:2001. More specifically, it can be measured by the method described in the examples.
[0048] The maximum peak height (Rp) conforming to JIS B0601:2001 is preferably 0.01 μm < Rp < 1.20 μm, 0.01 μm < Rp < 1.00 μm, and 0.01 μm < Rp < 0.90 μm. When Rp is within the above range, the film has excellent abrasion resistance and writing feel when information is input by a pen-type pointing device to a pen input device to which the film is attached. The maximum valley depth (Rv) conforming to JIS B0601:2001 can be measured in accordance with JIS B0601:2001. More specifically, it can be measured by the method described in the examples.
[0049] The maximum valley depth (Rv) and the maximum peak height (Rp) satisfy the relationship of 0.80 < Rv / (Rv + Rp) < 0.90, preferably 0.81 < Rv / (Rv + Rp) < 0.90. When Rv / (Rv + Rp) satisfies the above relationship, the film has excellent abrasion resistance and writing feel when information is input by a pen-type pointing device to a pen input device to which the film is attached.
[0050] The average length (RSm) of the elements conforming to JIS B0601:2001 is 30 μm < RSm < 300 μm, preferably 30 μm < RSm < 200 μm, 30 μm < RSm < 150 μm, 30 μm < RSm < 100 μm, and 30 μm < RSm < 90 μm. When RSm is within the above range, the film has excellent abrasion resistance and a tendency to have good writing feel when information is input by a pen-type pointing device to a pen input device with the film attached. The maximum valley depth (RSm) conforming to JIS B0601:2001 can be measured in accordance with JIS B0601:2001. More specifically, it can be measured by the method described in the examples.
[0051] The surface structure of the film may be formed by including fine particles on the surface of the film or may be formed without including fine particles on the surface of the film. From the viewpoint of improving abrasion resistance, it is preferably formed without including fine particles on the surface of the film.
[0052] The method for controlling Rv, Rp, and RSm is not particularly limited. For example, in the method for manufacturing the film described below, a method of adjusting the material, particle size, etc. of inorganic and / or organic fine particles fixed on the positive-type surface can be mentioned.
[0053] 2.2. Storage Elastic Modulus The storage elastic modulus of the film is 0.052 to 1.500 GPa, preferably 0.080 to 1.300 GPa, 0.150 to 1.000 GPa, and 0.150 to 0.900 GPa. When the storage elastic modulus of the film is within the above range, the film has excellent abrasion resistance and flexibility. The storage elastic modulus of the film can be measured by a known method. More specifically, it can be measured by the method described in the examples. Also, when the film of the present embodiment is a laminated film, the storage elastic modulus is the storage elastic modulus of the surface layer film.
[0054] The method for controlling the storage elastic modulus of the film is not particularly limited. For example, a method of controlling the composition of the UV curable resin composition can be mentioned.
[0055] 2.3.Thickness When the film of the present embodiment is a single-layer film, the average thickness of the film of the present embodiment is not particularly limited, but is, for example, 20 to 800 μm, 50 to 500 μm, 75 to 300 μm, or 100 to 200 μm. When the film thickness is within the above range, the film tends to be excellent in abrasion resistance and bending property.
[0056] When the film of the present embodiment is a laminated film consisting of a surface layer film made of a UV-curable resin composition and a base film supporting the surface layer film, the average thickness of the base film is not particularly limited, but is, for example, 1 to 500 μm, 50 to 400 μm, or 100 to 300 μm. The average thickness of the surface layer film is not particularly limited, but is, for example, 10 to 300 μm, 50 to 250 μm, 75 to 200 μm, or 75 to 150 μm. When the thicknesses of the surface layer film and base film of the film are within the above ranges, the film of the present embodiment tends to be excellent in abrasion resistance and bending properties.
[0057] The thickness of the film can be measured by a known method, for example, using a micrometer, though the method is not particularly limited.
[0058] 3. Film manufacturing method The method for producing a film according to the present embodiment includes a coating step of coating a UV-curable resin composition, and a positive transfer step of forming a surface structure of the film by transfer using a positive mold.
[0059] 3.1.Coating process When the film according to the present embodiment is a single-layer film, the method is not particularly limited, but for example, an uncured UV-curable resin composition is applied onto a UV-transmitting substrate.When the film according to the present embodiment is a laminated film consisting of a surface layer film made of a UV-curable resin composition and a substrate film supporting the surface layer film, the method is not particularly limited, but for example, an uncured UV-curable resin composition is applied onto the substrate film.
[0060] The UV transparency is not particularly limited, but may be, for example, a property of transmitting 10% or more, 30% or more, 50% or more, or 70% or more of ultraviolet light having a wavelength of 365 nm.
[0061] The uncured UV-curable resin composition is applied by a known method, which is not particularly limited, but includes, for example, gravure coating, reverse coating, comma coating, die coating, bar coating, curtain flow coating, roller coating, spraying, airless spraying, and hot spraying.
[0062] The coating step may be performed after diluting the UV-curable resin composition with a solvent. The solvent is not particularly limited, but may be, for example, a non-polar solvent or a polar solvent.
[0063] 3.2.Positive transfer process The positive mold is a mold for producing the film according to the present embodiment, and has a concave-convex shape on its surface region. The method for imparting the concave-convex shape to the surface region of the positive mold is not particularly limited, but examples thereof include a method of fixing inorganic and / or organic fine particles to the surface region of the positive mold, and a method of producing a positive mold so that the surface region of the positive mold has a concave-convex shape.
[0064] The positive mold may have a single layer structure or a multi-layer structure. In the case of a multi-layer structure, it may include a base layer, a rough surface layer on the base layer, and a release layer on the rough surface layer, and the rough surface layer and the release layer constitute the surface region of the positive mold. The rough surface layer gives an uneven shape to the surface region of the positive mold, and the release layer makes it easy to remove the positive mold in the film manufacturing method described later.
[0065] When the positive type has a single-layer structure, it includes, but is not limited to, for example, the UV-curable resin detailed in 1.1, the thermosetting resin detailed in 1.4, the thermoplastic resin detailed in 1.4, and / or inorganic materials such as metal and glass.
[0066] When the positive type has a multi-layer structure, the base layer includes, but is not limited to, for example, a UV-curable resin as described in detail in 1.1, a thermosetting resin as described in detail in 1.4, a thermoplastic resin as described in detail in 1.4, and / or an inorganic material such as metal or glass.
[0067] When the positive type has a multi-layer structure, the rough surface layer is not particularly limited, and may contain, for example, a UV-curable resin as described in detail in 1.1., a thermosetting resin as described in detail in 1.4., a thermoplastic resin as described in detail in 1.4., and / or an inorganic material such as metal or glass, and may contain inorganic and / or organic fine particles.
[0068] When the positive mold has a multi-layer structure, the release layer is not particularly limited, and may contain, for example, a UV-curable resin as described in detail in 1.1., a thermosetting resin as described in detail in 1.4., a thermoplastic resin as described in detail in 1.4., and / or an inorganic material such as metal or glass, and may also contain a release agent such as a silicone-based release agent.
[0069] The inorganic and / or organic fine particles fixed to the positive surface region are not particularly limited, but may be, for example, a metal element, a metal compound, a silicon compound, a fluorine compound, particles formed from a thermoplastic resin, particles formed from a thermosetting resin, or particles formed from a photocurable resin.
[0070] The particle size of the inorganic and / or organic fine particles fixed to the positive surface region is preferably 0.5 to 40.0 μm, 1.0 to 20.0 μm, or 2.0 to 10.0 μm. When the particle size of the fine particles is within the above numerical range, a film satisfying the characteristics detailed in 2. Film Characteristics can be easily formed.
[0071] The maximum valley depth (Rv) of the positive surface area in accordance with JIS B0601:2001 is preferably 0.01 μm. <Rv<1.20μmであり、0.01μm<Rv<1.10μmである。
[0072] The maximum peak height (Rp) of the positive surface area in accordance with JIS B0601:2001 is preferably 1.50 μm. <Rp<8.00μmであり、2.00μm<Rp<7.50μmであり、2.50μm<Rp<7.00μmである。
[0073] The maximum valley depth (Rv) and maximum peak height (Rp) of the positive mold are preferably within 0.01 <Rv / (Rv+Rp)<0.20であり、0.10<Rv / (Rv+Rp)<0.15である。
[0074] The positive surface area preferably has an average element length (RSm) according to JIS B0601:2001 of 30 μm. <RSm<300μmであり、30μm<RSm<200μmであり、30μm<RSm<150μmであり、30μm<RSm<100μmであり、30μm<RSm<90μmである。
[0075] When the positive type surface area satisfies the above numerical range, a film satisfying the properties detailed in 2. Film Properties can be easily formed.
[0076] The positive type may contain other known components. The other components are not particularly limited, but may include colorants, antioxidants, photopolymerization accelerators, ultraviolet absorbers, light stabilizers, flame retardants, fillers, mold release agents, and other additives. The other components may be used alone or in combination of two or more.
[0077] The method of transferring the shape of the surface region of the positive mold to produce the film of this embodiment is not particularly limited, but for example, after the coating process, the positive mold is laminated on the uncured UV-curable resin composition, and UV is irradiated from the substrate, substrate film, or positive mold side to cure the UV-curable resin composition with the uneven shape of the surface region of the positive mold transferred. Thereafter, the positive mold is removed, and the film according to this embodiment can be produced.
[0078] The light source for UV irradiation is not particularly limited, but examples thereof include a mercury lamp, a high-pressure mercury lamp, a UV-LED, a xenon lamp, and a laser light source.
[0079] The intensity and integrated intensity of UV irradiation are appropriately selected depending on the composition, thickness, etc. of the UV-curable resin composition. The intensity of UV irradiation is not particularly limited, but is, for example, 10 mW / cm 2 ~10000mW / cm 2 The integrated intensity of UV irradiation is not particularly limited, but is, for example, 50 to 10,000 mJ / cm. 2 It is.
[0080] 4. Pen-type pointing device A pen-type pointing device is a device for inputting information such as characters to a pen input device, and is made of hard materials such as plastics and metals. Examples of plastics include, but are not limited to, polyamide, polyacetal, polycarbonate, and polyphenylene ether. Examples of metals include, but are not limited to, metals such as iron and aluminum, and alloys such as stainless steel. Each of these may be used alone or in combination of two or more.
[0081] The shape of the pen tip is not particularly limited, but is usually a curved shape. The average diameter of the pen tip is not particularly limited, but is, for example, 0.1 to 10.0 mm. EXAMPLES
[0082] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.
[0083] 1. Film Preparation 1.1. Preparation of films (negative films) of Examples 1 to 5 and Comparative Examples 1 and 2 A UV-curable resin composition was prepared by mixing the components to obtain the composition shown in Table 1. A matte release film manufactured by Otsuki Kogyo Co., Ltd. was prepared as a positive mold. The matte release film is configured by laminating a substrate layer having a thickness of 25 μm, a rough surface layer made of "GM60" manufactured by Otsuki Kogyo Co., Ltd. containing silica filler, and a release layer made of "SK-1" manufactured by Otsuki Kogyo Co., Ltd., which is a silicone-based release coat, in this order. A UV-curable resin composition was applied onto this positive mold by die coating, and a polyethylene terephthalate film (Cosmoshine A4360 manufactured by Toyobo Co., Ltd., thickness 188 μm) was laminated as a substrate film on the applied UV-curable resin composition. This laminate was passed between two metal rolls having a gap of a certain distance, and the UV-curable resin composition was spread between the positive mold and the substrate film so that the thickness was uniform. The gap was appropriately adjusted so that the thickness of the UV-curable composition layer after curing was 100 μm. The thickness of the positive mold was measured with a micrometer. Next, a high-pressure mercury lamp (Oak Manufacturing Co., Ltd., HHM-7000 / D-FS) was used to irradiate the substrate film with an intensity of 150 ± 10 mW / cm. 2 , cumulative irradiation intensity 3000±300mJ / cm 2 The UV-curable resin composition was cured by irradiating it with ultraviolet light having a main wavelength of 365 nm so that the surface layer film was formed and cured, and the surface structure of the film was formed. The intensity of the ultraviolet light was measured using UVR-T1 / UD-T36 manufactured by Topcon Corporation. The measurement conditions were a measurement wavelength of 300 to 390 nm and a peak sensitivity wavelength of 355 nm. The positive type was then demolded to obtain the films (negative type films) of Examples 1 to 5 and Comparative Examples 1 to 2.
[0084] The maximum valley depth (Rv) of the valley, the maximum peak height (Rp) of the peak, and the average length of the elements (RSm) of the positive type, according to JIS B0601:2001, were Rv = 1.02 μm, Rp = 4.25 μm, and RSm = 68.52 μm, respectively. Also, Rv / (Rv + Rp) = 0.19. Rv, Rp, and RSm were measured by the method described below.
[0085] 1.2. Preparation of films (positive type films) of Comparative Examples 3 to 9 UV-curable resin compositions were prepared by mixing to obtain the compositions shown in Table 2. The positive molds prepared for producing the films of Examples 1 to 5 and Comparative Examples 1 and 2 were placed on a 300 mm × 200 mm stainless steel tray with a rim height of 10 mm, with the surface opposite to the surface region (convex shape) facing the bottom of the stainless steel tray. Then, a silicone rubber liquid prepared by mixing the silicone rubber base material "TSE3455T(A)" manufactured by Momentive Performance Materials Japan, LLC, the silicone rubber curing agent "TSE3455T(B)" manufactured by Momentive Performance Materials Japan, LLC, and the silicone rubber curing retarder "ME75" manufactured by Momentive Performance Materials Japan, LLC, in a weight ratio of "TSE3455T(A)": "TSE3455T(B)": "ME75" = 100:10:1 was poured into the stainless steel so that the thickness after curing was 5 mm, and after vacuum degassing, it was placed in a 55°C oven for 7 hours to perform the primary curing. Next, the silicone rubber that had undergone the primary curing was peeled off from the positive mold and the stainless steel tray, and the peeled silicone rubber was placed in a 100°C oven for 20 hours to perform the secondary curing, and a negative mold was obtained. A UV-curable resin composition was applied onto this negative mold by die coating, and a polyethylene terephthalate film (Cosmoshine A4360, thickness 188 μm, manufactured by Toyobo Co., Ltd.) was laminated onto the applied UV-curable resin composition as a substrate film. This laminate was passed between two metal rolls having a gap of a certain distance, so that the UV-curable resin composition was spread between the negative mold and the substrate film so that the thickness was uniform. The gap was appropriately adjusted so that the thickness of the UV-curable composition layer after curing was 100 μm. The thickness of the negative mold was measured with a micrometer. Next, a high-pressure mercury lamp (HHM-7000 / D-FS, manufactured by Oak Manufacturing Co., Ltd.) was used from the substrate film side, with an irradiation intensity of 150±10 mW / cm 2 , cumulative irradiation intensity 3000±300mJ / cm 2The UV-curable resin composition was cured by irradiating it with ultraviolet light having a main wavelength of 365 nm so as to obtain a surface layer film, which was then molded and cured to form a surface structure of the film. The intensity of the ultraviolet light was measured using a UVR-T1 / UD-T36 manufactured by Topcon Corporation. The measurement conditions were a measurement wavelength of 300 to 390 nm and a peak sensitivity wavelength of 355 nm. The positive mold was then demolded to obtain the films (positive-type films) of Comparative Examples 3 to 9.
[0086] 1.3. Preparation of film for measuring storage modulus The storage modulus shown in Tables 1 and 2 was measured by forming a film from the same UV-curable resin composition as in the films of each of the Examples and Comparative Examples using the method described below, and then measuring the resulting film using the method described below.
[0087] Specifically, the UV-curable resin composition was prepared by mixing the ingredients so as to have the composition shown in Tables 1 and 2. The UV-curable resin composition was applied to the release surface of a release polyethylene terephthalate film A (PET3811, manufactured by Lintec Corporation) by die coating, and a release polyethylene terephthalate film B (PET3811, manufactured by Lintec Corporation) was laminated on the applied UV-curable resin composition so that the release surface was in contact with the UV-curable resin composition, and the UV-curable resin composition was spread between the release polyethylene terephthalate film A and the release polyethylene terephthalate film B so that the thickness was uniform through two metal rolls having a gap of a certain distance. The gap was appropriately adjusted so that the thickness of the UV-curable composition layer after curing was 100 μm. Next, a high-pressure mercury lamp (HHM-7000 / D-FS, manufactured by Oak Manufacturing Co., Ltd.) was used from the film B side to irradiate the film with an irradiation intensity of 150±10 mW / cm. 2 , cumulative irradiation intensity 3000±300mJ / cm 2 The UV-curable resin composition was cured by irradiating it with ultraviolet light having a dominant wavelength of 365 nm so that the UV-curable resin composition was cured. The intensity of the ultraviolet light was measured using a UVR-T1 / UD-T36 manufactured by Topcon Corporation. The measurement conditions were a measurement wavelength of 300 to 390 nm and a peak sensitivity wavelength of 355 nm. Subsequently, Film A and Film B were peeled off from the cured UV-curable resin composition to obtain a film for measuring the storage modulus.
[0088] The materials shown in Tables 1 and 2 are as follows. [(Meth)acrylate oligomer] Urethane acrylate oligomer: Daicel-Allnex Corporation "KRM7735" [(Meth)acrylate monomer] Isobornyl acrylate monomer: "IBXA" manufactured by Kyoeisha Chemical Co., Ltd. Tripropylene glycol diacrylate monomer: "TPGDA" manufactured by Daicel-Allnex Corporation Tetrahydrofurfuryl acrylate monomer: "THF-A" manufactured by Kyoeisha Chemical Co., Ltd. Phenoxyethyl acrylate monomer: "PO-A" manufactured by Kyoeisha Chemical Co., Ltd. Dipentaerythritol hexaacrylate monomer: "DPHA" manufactured by Daicel Allnex Corporation [Photopolymerization initiator] 1-Hydroxycyclohexyl phenyl ketone: "Omnirad184" manufactured by IGM Resins BV Diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide: "TPO" manufactured by IGM Resins BV
[0089] 2.Measurement method 2.1.Surface roughness parameters For the films and positive type produced in each of the Examples and Comparative Examples, 0.5 mm thick soda lime glass was attached and fixed via an adhesive to the surface opposite to the film surface (measurement surface), and the maximum valley depth (Rv), maximum peak height (Rp), and average element length (RSm) were measured using a surface roughness measuring device (Tokyo Seimitsu Co., Ltd., SURFCOM TOUCH50) under the following conditions in accordance with JIS B0601:2001. Stylus for detecting surface roughness: Tokyo Seimitsu Co., Ltd., DM43801 (tip radius: 2 μm) ·Measurement speed: 1.5mm / s Evaluation length: 4mm Measurement type: Roughness measurement ·Shape removal: R surface Cutoff type: Gaussian Cutoff frequency λc: 0.8mm Cutoff frequency λs: 2.5μm
[0090] 2.2.Storage modulus The storage modulus of the film was measured using a dynamic viscoelasticity measuring device, DMA (Dynamic Mechanical Analysis, RSA-G2, manufactured by TA Instruments Co., Ltd.) The measurement conditions were tensile mode, heating rate of 10°C / min, and 1Hz, and the value at 25°C was read.
[0091] 2.3. Thickness of surface layer film The thickness of the laminate film prepared in 1.1. and 1.2., in which the surface layer film and the base film were laminated, was measured with a micrometer, and the thickness of the surface layer film was calculated by subtracting the thickness of the base film measured beforehand from the measured thickness.
[0092] 3. Evaluation 3.1.Abrasion resistance evaluation A Wacom hard felt core ACK-20003 was attached to a reciprocating abrasion tester Tribogear TYPE30 manufactured by Shinto Chemical Industry Co., Ltd., and the hard felt core was brought into contact with the surface of the film produced in each Example and Comparative Example. After that, the surface of the film was reciprocated 500 times and 1000 times with a load of 100 g, a speed of 3000 mm / min, and a moving distance of 50 mm in an atmosphere of 23°C and 65% (relative humidity), and visually evaluated according to the following criteria. [Evaluation Criteria] ◯: No scratches were observed on the film surface after 500 and 1000 reciprocations. △: No scratches were observed after 500 strokes, but scratches were observed on the film surface after 1000 strokes. This is at a level that is not problematic for practical use. ×: After 500 round trips, scratches occurred on the film surface.
[0093] 3.2. Writing feel evaluation The films prepared in each of the Examples and Comparative Examples were evaluated by sensory evaluation using a stylus pen Hi-uni DIGITAL for Wacom manufactured by Mitsubishi Pencil Co., Ltd., according to the following criteria. [Evaluation Criteria] Good: There is moderate writing resistance, allowing for smooth writing. Δ: The writing resistance is slightly larger (or smaller) than the appropriate range, making it difficult to write smoothly. This is at a level that is problematic for practical use. ×: The writing resistance is significantly larger (or smaller) than the appropriate range, making it impossible to write smoothly. This is at a level that is problematic for practical use.
[0094] 3.3.Flexibility evaluation The films prepared in each Example and Comparative Example were used to carry out a bending resistance test in accordance with the cylindrical mandrel method specified in JIS K5600-5-1:1999. Using a bending tester (manufactured by BEVS Industrial Co., Ltd., cylindrical mandrel bending tester), the surface layer film was wound around a cylindrical mandrel with a diameter of 10 mm so that the surface layer film was on the outside, and the surface layer film was visually observed to see if it had any cracks. In addition, the films prepared in each Example and Comparative Example, apart from those wound around the cylindrical mandrel, were visually observed to see if it had any cracks when bent 90° so that the surface layer film was on the outside, and were evaluated according to the following criteria. [Evaluation Criteria] ◯: No cracks were observed in the surface layer film when it was wrapped around the cylindrical mandrel and when it was bent at 90°. Δ: No cracks were observed in the surface layer film when it was wound around a cylindrical mandrel. When it was bent at 90°, cracks were observed in the surface layer film, but at a level that would not cause any practical problems. ×: Cracks were observed in the surface layer film both when it was wound around the cylindrical mandrel and when it was bent at 90°.
[0095] 3.4. Overall evaluation For the evaluation of abrasion resistance, writing feel, and flexibility, ◯ was assigned 2 points, △ was assigned 1 point, and × was assigned 0 point. The total score of all evaluation results was calculated for each example and comparative example, and an overall evaluation was made according to the following criteria. [Evaluation Criteria] ◎:6 points 〇:5 points △:4 points ×: 0~3 points
[0096] Tables 1 and 2 show the compositions of the UV-curable resin compositions used to prepare the films in the examples and comparative examples, the measured values of the physical properties, and the evaluation results.
[0097] [Table 1] *1: The values shown are, from the left, solid content mass ratio / mass percentage (%) of the total solid content of the UV-curable resin composition / mass percentage (%) of the total solid content of the UV-curable resin.
[0098] [Table 2] *1: The values shown are, from the left, solid content mass ratio / mass percentage (%) of the total solid content of the UV-curable resin composition / mass percentage (%) of the total solid content of the UV-curable resin.
[0099] 4. Evaluation Results The evaluation results in Tables 1 and 2 show that all of Examples 1 to 5 are superior in abrasion resistance, writing feel, and flexibility compared to Comparative Examples 1 and 2 in which the storage modulus is outside the specified range, and Comparative Examples 3 to 9 in which any of Rv, Rv / (Rv+Rp), and RSm is outside the specified range.
Claims
1. A film having a surface having valleys and peaks conforming to JIS B0601:2001, The maximum valley depth (Rv) of the valley, the maximum peak height (Rp) of the peak, and the average length (RSm) of the element in accordance with JIS B0601:2001, 1.50μm<Rv<8.00μm 0.80<Rv / (Rv+Rp)<0.90 30μm<RSm<300μm Fulfilling The storage modulus of the film is 0.052 GPa to 1.500 GPa; The film includes a UV-curable resin. film.
2. does not contain particulates to form said valleys and / or peaks on said surface; The film of claim 1.
3. The storage modulus of the film is 0.150 GPa to 1.000 GPa. The film according to claim 1 or 2.
4. The UV curable resin includes at least one selected from the group consisting of (meth)acrylate oligomers and (meth)acrylate monomers. The film according to claim 1 or 2.
5. The (meth)acrylate oligomer includes at least one selected from the group consisting of a urethane (meth)acrylate oligomer, an acrylic resin (meth)acrylate oligomer, an epoxy (meth)acrylate oligomer, and a polyester (meth)acrylate oligomer; The (meth)acrylate monomer includes at least one selected from the group consisting of isobornyl (meth)acrylate monomer, tripropylene glycol di(meth)acrylate monomer, tetrahydrofurfuryl (meth)acrylate monomer, phenoxyethyl (meth)acrylate monomer, dipentaerythritol hexa(meth)acrylate monomer, tricyclodecane dimethanol di(meth)acrylate monomer, benzyl (meth)acrylate monomer, stearyl (meth)acrylate monomer, isodecyl (meth)acrylate monomer, isoctyl (meth)acrylate monomer, 1,6-hexanediol di(meth)acrylate monomer, lauryl (meth)acrylate monomer, m-phenoxybenzyl (meth)acrylate monomer, isoamyl (meth)acrylate monomer, phenoxydiethylene glycol (meth)acrylate monomer, and 1,4-butanediol di(meth)acrylate monomer; The film of claim 4.
6. The film further comprises a photoinitiator. The film according to claim 1 or 2.
7. A film for a pen input device. The film according to claim 1 or 2.
8. A method for producing a film, comprising: a coating step of coating a UV-curable resin composition; and a step of forming valleys and peaks in accordance with JIS B0601:2001 on a surface of the film by transfer using a positive mold, The film has a maximum valley depth (Rv) of the valley, a maximum peak height (Rp) of the peak, and an average element length (RSm) in accordance with JIS B0601:2001. 1.50μm<Rv<8.00μm 0.80<Rv / (Rv+Rp)<0.90 30μm<RSm<300μm Fulfilling The storage modulus of the film is 0.052 GPa to 1.500 GPa; The film includes a UV-curable resin. A method for manufacturing a film.
Citation Information
Patent Citations
Laminated film for touch panel
JP2010153298A
Touch feeling improved film and method for manufacturing the same
JP2014137640A
Pen input surface material, polarizing plate and display device
JP2019057141A
Cured film, laminate, and method for producing the same
JP2022025620A
Surface material for pen input device
WO2020213156A1